Basic approximations for large scale motion in equatorial regions - YAJNIK, KIRIT S. (MAUSAM, 1978)
An exploratory study of approximations for the equatorial region is given to stress the rapid variation of coriolis parameter with latitude, and the consequential differences in the length scales in meridional and zonal directions. The resulting equations retain coriolis as well as non-linear inertia terms in zonal momentum balance. This approximation for dominantly zonal flow is supplemented with another for a sublayer near the equator where the meridional flow might be dominant in case of large interhemispheric transport, as in monsoon over the Indian Ocean.